Application of PANI/TiO2 composite for photocatalytic degradation of contaminants from aqueous solution - Lee, Youn Jun; Lee, Hae Su; Lee, Chang Gu; Park, Seong Jik; Lee, Jechan; Jung, Seungho; Shin, Gwy Am (Applied Sciences (Switzerland), 2020)
Polyaniline (PANI) is a promising conducting polymer for surface modification of TiO2 to achieve extended photoresponse to visible light and increased photocatalytic efficiency. In this study, we report the synthesis of a PANI/TiO2 composite with different weight ratios of PANI, which was subsequently employed for photocatalytic degradation of methylene blue (MB), bisphenol A (BPA), and bacteriophage MS2 under visible-light irradiation. The functional groups, morphology, and light response of the composite were characterized by Fourier-transform infrared spectroscopy, field-emission transmission electron microscopy, and diffuse reflectance UV-visible spectroscopy, respectively. The PANI/TiO2 composite containing 4% by weight ratio of PANI was most suitable for MB degradation, and this photocatalyst was very stable even after repeated use (four cycles). The degradation of BPA and bacteriophage MS2 by PANI/TiO2 composite reached 80% in 360 min and 96.2% in 120 min, respectively, under visible-light irradiation. Therefore, the PANI/TiO2 composite with enhanced visible-light photocatalytic efficiency and stability can be widely used for the degradation of water contaminants.
Keywords: Photocatalyst; Polyaniline; Titanium dioxide; Visible-light irradiation; Water contaminant